Overdiagnosis of malaria in patients with severe febrile illness in Tanzania: a prospective study. Issue 7476 (12th November 2004) - Reyburn, Hugh; Mbatia, Redepmta; Drakeley, Chris; Carneiro, Ilona; Mwakasungula, Emmanuel; Mwerinde, Ombeni; Saganda, Kapalala; Shao, John; Kitua, Andrew; Olomi, Raimos; Greenwood, Brian M; Whitty, Christopher J M
Abstract: Objective To study the diagnosis and outcomes in people admitted to hospital with a diagnosis of severe malaria in areas with differing intensities of malaria transmission. Design Prospective observational study of children and adults over the course a year. Setting 10 hospitals in north east Tanzania. Participants 17 313 patients were admitted to hospital; of these 4474 (2851 children aged under 5 years) fulfilled criteria for severe disease. Main outcome measure Details of the treatment given and outcome. Altitudes of residence (a proxy for transmission intensity) measured with a global positioning system. Results Blood film microscopy showed that 2062 (46.1%) of people treated for malaria had Plasmodium falciparum (slide positive). The proportion of slide positive cases fell with increasing age and increasing altitude of residence. Among 1086 patients aged ≥ 5 years who lived above 600 metres, only 338 (31.1%) were slide positive, while in children < 5 years living in areas of intense transmission (< 600 metres) most (958/1392, 68.8%) were slide positive. Among 2375 people who were slide negative, 1571 (66.1%) were not treated with antibiotics and of those, 120 (7.6%) died. The case fatality in slide negative patients was higher (292/2412, 12.1%) than for slide positive patients (142/2062, 6.9%) (P < 0.001). Respiratory distress and altered consciousness were the strongest predictors of mortality in slide positive and slide negative patients and in adults as well as children. Conclusions In Tanzania, malaria is commonly overdiagnosed in people presenting with severe febrile illness, especially in those living in areas with low to moderate transmission and in adults. This is associated with a failure to treat alternative causes of severe infection. Diagnosis needs to be improved and syndromic treatment considered. Routine hospital data may overestimate mortality from malaria by over twofold.